Income Smoothing, Earnings Management and the Credibility of Accounting Information - OGUNDAJO, Grace Oyeyemi; ASAOLU, Taiwo; AJAYI, Ademola; OTITOLAIYE, Emmanuel Dare; OGUNFOWORA, Afolake (International Journal of Business, Economics and Management, 2021)
This study investigated the effect of income smoothing and earning management on the credibility of accounting information of listed manufacturing companies in Nigeria. Data used were extracted from the annual reports and accounts of the selected sixteen (16) firms for a period of 10 years (2010-2019) while content analysis was adopted in measuring accounting information credibility. Multiple linear regression analysis (OLS) method was adopted for the analysis. The result revealed that income smoothing and earnings management had statistically insignificant effect on fundamental qualitative characteristics (FQC), while income smoothing and earnings management had statistically significant effect on enhancing qualitative characteristics (EQC). However, the study obtained that income smoothing and earnings management had positive and significant effect on the credibility of accounting information of the listed manufacturing companies in Nigeria. The study opined that managers should ensure that accounting information is credible, possesses desirable accounting information qualities of relevance, and faithful representation, also verifiable, comparable, understandability, and timeliness.